2016
DOI: 10.1016/j.scitotenv.2015.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic benefits of variable rate nitrogen fertilization in a nitrate vulnerable zone

Abstract: Agronomic input and management practices have traditionally been applied uniformly on agricultural fields despite the presence of spatial variability of soil properties and landscape position. When spatial variability is ignored, uniform agronomic management can be both economically and environmentally inefficient. The objectives of this study were to: i) identify optimal N fertilizer rates using an integrated spatio-temporal analysis of yield and site-specific N rate response; ii) test the sensitivity of site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 27 publications
3
79
1
2
Order By: Relevance
“…SALUS has been widely used (Basso and Ritchie, 2015) and successfully validated for Italian agricultural systems and environmental conditions by Basso et al (2007Basso et al ( , 2010Basso et al ( , 2011Basso et al ( , 2011bBasso et al ( , 2016.…”
Section: The Salus Modelmentioning
confidence: 99%
“…SALUS has been widely used (Basso and Ritchie, 2015) and successfully validated for Italian agricultural systems and environmental conditions by Basso et al (2007Basso et al ( , 2010Basso et al ( , 2011Basso et al ( , 2011bBasso et al ( , 2016.…”
Section: The Salus Modelmentioning
confidence: 99%
“…With the advancement of mechanized farming and control technologies, the operability and accuracy of VF has been significantly improved. Studies have demonstrated that variable rate fertilization is beneficial to increasing production and revenue, ensuring sustainable agricultural development and protecting the environment [3,4]. A reasonable prescription map is the key factor for VF application [5], and the SAN content is necessary in map making.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Anaerobic Digestion (AD) of different feedstock has proved to be an interesting energy source in rural areas [3], especially when the AD plants are fed with local available feedstock and the energy generated (i.e. heat) is used near the plant [4].…”
Section: Introductionmentioning
confidence: 99%